Large eddy simulation of two isothermal and reacting turbulent separated oxy-fuel jets. (15th March 2017) - Hidouri, A.; Chrigui, M.; Boushaki, T.; Sadiki, A.; Janicka, J.
Highlights: LES methodology of oxy-fuel combustion generated by two aligned jets is suggested and validated. Integration of FGM under oxy-fuel environment and chemistry/turbulence coupling via presumed PDF. Effect of oxygen on the FGM tabulation is pointed out as compared to NG/air combustion. Impact of combustion on flow and mixing field evolvement is pointed out. Analysis of interactions between the two jets in both non-reacting and reacting cases. Favorable comparison to laser-based experimental data. Abstract: In this work, a Large eddy simulation (LES) method and a tabulated chemistry approach according to the Flamelet Generated Manifold (FGM) strategy are coupled to numerically study the interactions of turbulent isothermal and reacting flows stemming from two aligned jets providing alternately fuel (natural gas) and oxidant (pure oxygen gas).The jets feature different geometries and deliver unequal momentums at the boundaries. The effect of oxygen in comparison to air environment on the FGM tabulation and results is pointed out. In addition, the impact of combustion on the flow and mixing field evolvement is analyzed. The LES relies on a dynamic Smagorinsky subgrid scale (SGS) model and a linear eddy diffusivity ansatz to close the SGS stresses and the SGS scalar fluxes for describing the turbulent flow field and the turbulent scalar field, respectively. For model assessment, available laser-based experimental data are used for model validation. In particular the numerical results are compared with available experimental data for the flow field. The latter are gained experimentally by the Particle Image Velocimetry (PIV) and laser tomography, respectively. In the first part of this paper, the jets interaction process is studied for the isothermal case while the oxy-fuel combustion in the reacting case is analyzed in the second part. The analysis is achieved in terms of statistical quantities for the flow velocity, mixture fraction, chemical species and temperature. An overall satisfactory agreement is reported.